Cascade DNA Circuits Mediated CRISPR‐Cas12a Fluorescent Aptasensor based on Multifunctional Fe3O4@hollow‐TiO2@MoS2 Nanochains for Tetracycline Determination. Issue 16 (22nd January 2023) - Lv, Yan; Sun, Yuhan; Zhou, You; Khan, Imran Mahmood; Niazi, Sobia; Yue, Lin; Zhang, Yin; Wang, Zhouping
Abstract: Herein, for the first time, the CRISPR‐Cas12a system is combined with aptamer, cascaded dynamic DNA network circuits, and Fe3 O4 @hollow‐TiO2 @MoS2 nanochains (Fe3 O4 @h‐TiO2 @MoS2 NCs) to construct an efficient sensing platform for tetracycline (TC) analysis. In this strategy, specific recognition of the target is transduced and amplified into H1‐H2 duplexes containing the specific sequence of Cas12a‐crRNA through an aptamer recognition module and the dual amplification dynamic DNA network. Subsequently, the obtained activated Cas12a protein non‐specifically cleaves the adjacent reporter gene ssDNA‐FAM to dissociate the FAM molecule from the quencher Fe3 O4 @h‐TiO2 @MoS2 NCs, resulting in the recovery of the fluorescence signal and further signal amplification. Particularly, the synthesized multifunctional Fe3 O4 @h‐TiO2 @MoS2 NCs composites also exhibit superb magnetic separability and photocatalytic degradation ability. Under optimal conditions, the aptasensor displays a distinct linear relationship with the logarithm of TC concentration, and the limit of detection is as low as 0.384 pg mL −1 . Furthermore, the results of spiked recovery confirm the viability of the proposed aptasensor for TC quantification in real samples. This study extends the application of the CRISPR‐Cas12a system in the field of analytical sensing and contributes new insights into the exploration of reliable tools for monitoring and treating hazards in food and environment. Abstract : Herein, for the first time, the CRISPR‐Cas12a system is combined with aptamer, cascaded dynamic DNA network circuits, and multifunctional Fe3 O4 @hollow‐TiO2 @MoS2 nanochains (Fe3 O4 @h‐TiO2 @MoS2 NCs) to construct an efficient signal amplification sensing platform for tetracycline (TC) analysis. Particularly, the Fe3 O4 @h‐TiO2 @MoS2 NCs composites also exhibit excellent magnetic separation and photocatalytic degradation capabilities, which contributes to their sustainability in this sensing platform.